Unusual Onset of Anti-NMDA-Receptor Encephalitis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
A 19-year-old female presented with vomiting, diarrhea, emotional lability, auditory hallucinations, expressive dysphasia, and delirium.